Chemical effects of CO2 dilution on CH4 and H2 spherical flame. (15th October 2019) - Wang, Du; Ji, Changwei; Wang, Shuofeng; Meng, Hao; Yang, Jinxin
Abstract: CO2 dilution is an effective strategy for combustion control. To understand the detailed dilution effects of CO2 (including physical effects and chemical effects) on CH4 and H2 combustion, an open-source CFD package laminarSMOKE was utilized to simulate the transient one-dimensional outwardly spherical flame combustion process in a closed chamber under 0–15% CO2 dilution mole fraction ( α ), at 293 K, 1 bar, stoichiometric ratio. The overall CO2 dilution effects decrease the unstretched/stretched flame propagation speed, maximum combustion pressure and prolong the combustion duration. In most conditions, physical effects play a dominant role and chemical effects amplify the dilution effects. Typically, the maximum combustion pressure of CH4 -CO2 -air flame at α = 15% reduces 1.15 bar compared with the undiluted case, the reduction percentage caused by physical and chemical effects is 12% and 1.5%, respectively. In addition, opposite overall effects of CO2 dilution on Markstein length ( L b ) of CH4 flames and H2 flame are performed. The physical effects of CO2 dilution increase the L b of CH4 flames but decrease that of H2 flames. Chemical effects are similar to physical effects for CH4 flames, but non-monotonic behavior is performed for H2 flame due to the combined effects of density ratio and mixture reactivity changes. Highlights: Chemical effects of CO2 dilution on laminar spherical flame were numerically study. Physical effects play leading roles in all changes of combustion properties. Chemical effects reduce flame propagation speed, maximum pressure, increase combustion duration. Chemical effects on Markstein length behave differently in CH4 and H2 flame.